Adoptive NK Cell Transfer as a Treatment in Colorectal Cancer Patients: Analyses of Tumour Cell Determinants Correlating With Efficacy In Vitro and In Vivo - Lanuza, Pilar M.; Alonso, M. Henar; Hidalgo, Sandra; Uranga-Murillo, Iratxe; García-Mulero, Sandra; Arnau, Raquel; Santos, Cristina; Sanjuan, Xavier; Santiago, Llipsy; Comas, Laura; Redrado, Sergio; Pazo-Cid, Roberto; et al. (Frontiers in Immunology, 2022)
Background Colorectal cancer (CRC) is a heterogeneous disease with variable mutational profile and tumour microenvironment composition that influence tumour progression and response to treatment. While chemoresistant and poorly immunogenic CRC remains a challenge, the development of new strategies guided by biomarkers could help stratify and treat patients. Allogeneic NK cell transfer emerges as an alternative against chemoresistant and poorly immunogenic CRC. Methods NK cell-related immunological markers were analysed by transcriptomics and immunohistochemistry in human CRC samples and correlated with tumour progression and overall survival. The anti-tumour ability of expanded allogeneic NK cells using a protocol combining cytokines and feeder cells was analysed in vitro and in vivo and correlated with CRC mutational status and the expression of ligands for immune checkpoint (IC) receptors regulating NK cell activity. Results HLA-I downmodulation and NK cell infiltration correlated with better overall survival in patients with a low-stage (II) microsatellite instability-high (MSI-H) CRC, suggesting a role of HLA-I as a prognosis biomarker and a potential benefit of NK cell immunotherapy. Activated allogeneic NK cells were able to eliminate CRC cultures without PD-1 and TIM-3 restriction but were affected by HLA-I expression. In vivo experiments confirmed the efficacy of the therapy against both HLA+ and HLA− CRC cell lines. Concomitant administration of pembrolizumab failed to improve tumour control. Conclusions Our results reveal an immunological profile of CRC tumours in which immunogenicity (MSI-H) and immune evasion mechanisms (HLA downmodulation) favour NK cell immunosurveillance at early disease stages. Accordingly, we have shown that allogeneic NK cell therapy can target tumours expressing mutations conferring poor prognosis regardless of the expression of T cell-related inhibitory IC ligands. Overall, this study provides a rationale for a new potential basis for CRC stratification and NK cell-based therapy.